Effects of shoe heel height on the end-point and joint kinematics of the locomotor system when crossing obstacles of different heights. Issue 3 (4th March 2017) - Chien, Hui-Lien; Lu, Tung-Wu
Abstract: High-heeled shoes increase the risk of falling during walking, especially in the presence of obstacles. The study aimed to compare the end-point (foot/shoe) trajectories and joint angles of the lower extremities in 12 healthy females crossing obstacles of different heights while barefoot and when wearing narrow-heeled shoes (heel heights: 3.9, 6.3 and 7.3 cm). During obstacle-crossing, young females in narrow-heeled shoes maintained the same leading toe-clearance as when barefoot, irrespective of the heel height, primarily through increased plantarflexion of the leading swing ankle. However, the shoe heel-clearance was significantly reduced when compared with barefoot, presumably related to the difficulty in precisely sensing the position of the shoe-heel tip. With an increasing obstacle height, the toe-clearance, heel-clearance and shoe heel-clearance were reduced linearly, indicating an increasing risk of tripping over the obstacle. The results will be helpful for the design and development of strategies to reduce the risk of falling when wearing narrow-heeled shoes. Practitioner Summary: Knowledge of the influence of narrow-heeled shoes and obstacles on lower limb joint and end-point kinematics helps in shoe design to address fall risks. Compared to barefoot, narrow-heeled shoes reduced shoe heel-clearances, which were further reduced linearly with increasing obstacle height, indicating an increasing risk of tripping over the obstacle.